Technology Disruptions in International Relations: The Needs for Cyber Diplomacy by Indonesia - Arindha Nityasari (Institute of International Studies, 2020)
The research will discuss about the impacts of technology disruption in international relations. This study aims to increase awareness about several disrupted areas in international politics, particularly in security niche. It will also examine technology disruptions in Indonesia as one of the Global South countries and see the gaps between South and North relations in the field of cyber security. This article also argues that multidiscipline and multi-stakeholder approach through cyber diplomacy is the most feasible solution to tackle the issues arising from technology disruption.